Effect of chicken egg yolk antibodies (IgY) against diarrhea in domesticated animals: a systematic review and meta-analysis. - Thirumalai Diraviyam; Bin Zhao; Yuan Wang; Ruediger Schade; Antonysamy Michael; Xiaoying Zhang; Xiaoying Zhang (PLoS ONE)
Background IgY antibodies are serum immunoglobulin in birds, reptiles and amphibians, and are transferred from serum to egg yolk to confer passive immunity to their embryos and offspring. Currently, the oral passive immunization using chicken IgY has been focused as an alternative to antibiotics for the treatment and control of diarrhea in animals and humans. This systematic review was focused to determine the effect of IgY in controlling and preventing diarrhea in domesticated animals including Piglets, Mice, Poultry and Calves. Methods and results Previous research reports focused on treatment effect of Chicken IgY against diarrhea were retrieved from different electronic data bases (MEDLINE, EMBASE, SPRINGER-LINK, WILEY, AGRICOLA, MEDWELL Journals, Scientific Publish, Chinese articles from Core periodicals in 2012). A total of 61 studies in 4 different animal classes met the inclusion criteria. Data on study characteristics and outcome measures were extracted. The pooled relative risk (RR) of 49 studies of different animals [Piglets--22; Mice--14; Poultry--7 and Calves--6] in meta-analyses revealed that, IgY significantly reduced the risk of diarrhea in treatment group when compare to the placebo. However, the 95% confidence intervals of the majority of studies in animal class piglets and calves embrace RR of one. The same results were obtained in sub group analyses (treatment regiment--prophylactic or therapeutic; pathogen type--bacterial or viral). Perhaps, this inconsistency in the effect of IgY at the individual study level and overall effect measures could be influenced by the methodological heterogeneity. Conclusion The present systematic review (SR) and meta-analysis demonstrated the beneficial effect of IgY. This supports the opinion that IgY is useful for prophylaxis and treatment. However, more intensive studies using the gold standard animal experiments with the focus to use IgY alone or in combination with other alternative strategies are indispensable.